2019
DOI: 10.1002/jsfa.9815
|View full text |Cite
|
Sign up to set email alerts
|

Remediated marine sediment as growing medium for lettuce production: assessment of agronomic performance and food safety in a pilot experiment

Abstract: BACKGROUND The use of reclaimed dredged sediments as growing media may offer a profitable alternative to their disposal as a waste and at the same time meets the need of peat‐substitute substrates in horticulture. When sediments are reused to cultivate food crops, issues related to human health rise due to potential accumulation of contaminants in the product. This pilot study aimed at verifying the suitability of a reclaimed dredged port sediment, used pure or mixed with peat, as a growing medium for lettuce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
(79 reference statements)
3
13
0
Order By: Relevance
“…Whole fruits, arils and peel total weight followed a common trend with PQ-0 > PQ-50 > PQ-100 in both the years. These findings clearly indicate that the physical and chemical composition of the sediments (Table 1), different from peat, induced plant stress resulting in a lower plant productivity as previously highlighted [12,18].…”
Section: Morphological Characteristics Of Purple Queen ® Fruitssupporting
confidence: 71%
See 1 more Smart Citation
“…Whole fruits, arils and peel total weight followed a common trend with PQ-0 > PQ-50 > PQ-100 in both the years. These findings clearly indicate that the physical and chemical composition of the sediments (Table 1), different from peat, induced plant stress resulting in a lower plant productivity as previously highlighted [12,18].…”
Section: Morphological Characteristics Of Purple Queen ® Fruitssupporting
confidence: 71%
“…To meet sustainability criteria in the plant nursery industry, attention is currently focused on the reutilization of waste-derived substrates. Among these, dredged remediated sediments have already been proposed as soilless growing media for the cultivation of ornamental and food crops [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the GM characteristics could affect the yield crop, therefore, to the main function of the system analyzed, in this case, 1 kg of fruit produced at the farm has been selected as the FU [22]. The adequacy of the FU selected is based on previous works developed by the same research group, where it was reported that the GM used did not affect the fruit quality and/or composition [23,24]. Therefore, the kg of fruits represents an equivalent function in all the alternative systems considered (Figure 1).…”
Section: Goal and Scope And Functional Unitmentioning
confidence: 99%
“…To model the sediment extraction phase (Table 3), the data provided by Kemp [26] were used. The AGRIPORT and HORTISED LIFE projects and bibliographic data were used to include the date of phytoremediation and landfarming [9,24]. The data extraction of peat is provided by Ecoinvent and quantifies the directly affected area, the electricity requirements and the diesel used for the mining operation and the extraction.…”
Section: Study System Descriptionmentioning
confidence: 99%
“…In these cases, the dredged sediment could be considered a resource rather than a residue able to reuse and revalorise from the circular economy perspective [7]. Thus, recent multidisciplinary scientific studies have reported, demonstrated and confirmed the viability of obtaining a new safe substrate from the treated dredged sediments related to the amounts of contaminants present in it [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%